2017
DOI: 10.4103/ijmy.ijmy_140_17
|View full text |Cite
|
Sign up to set email alerts
|

The most frequent Mycobacterium tuberculosis complex families in mali (2006–2016) based on spoligotyping

Abstract: Objective To identify strains of Mycobacterium tuberculosis complex (MTBc) circulating in Bamako region during the past 10 years. Materials and Methods From 2006 to 2016, we conducted a cross-sectional study to identify with spoligotyping, clinical isolates from tuberculosis (TB)-infected patients at different stages of their treatments in Bamako, Mali. Results Among the 904 suspected TB patients included in the study and thereafter tested in our BSL-3 laboratory, 492 (54.4%) had MTBc and therefore underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In this study we estimated a relatively unbiased population structure of the MTBc in consecutive smear positive new adult TB patients from Bamako district, and identified differential smear conversion by MTBc lineage. Our prevalence estimates of the different MTBc lineages correspond with earlier and smaller studies based on convenience sampling, with predominance of L4 (57%) and L6 (22.9%), while L1, L2, L3, and L5 are all present at less than five percent[4,10]. Counter to our hypothesis that L6 would respond better to TB treatment, we found that patients diseased with L6 rather experienced slower smear conversion than L4, not only with AR staining- which will stain dead bacilli too- but also with FDA vital stain microscopy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study we estimated a relatively unbiased population structure of the MTBc in consecutive smear positive new adult TB patients from Bamako district, and identified differential smear conversion by MTBc lineage. Our prevalence estimates of the different MTBc lineages correspond with earlier and smaller studies based on convenience sampling, with predominance of L4 (57%) and L6 (22.9%), while L1, L2, L3, and L5 are all present at less than five percent[4,10]. Counter to our hypothesis that L6 would respond better to TB treatment, we found that patients diseased with L6 rather experienced slower smear conversion than L4, not only with AR staining- which will stain dead bacilli too- but also with FDA vital stain microscopy.…”
Section: Discussionsupporting
confidence: 88%
“…Most studies on the MTBc population structure in the West African region were based on convenience sampling at referral centers, rather than sampling representative of the general TB population[9,10]. This potential for selection bias, combined with the higher risk for L6 to be missed in culture, has complicated estimates of the prevalence of L6 over time[10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated, a priori, that 20 participants each would be needed in the MAF and MTB groups to achieve 80% power with a two-sided significant level (α) of 0.05, and at a 95% confidence level. We assumed based on previous studies [4,32], that 42% of patients are exposed/likely to be MAF-infected, with an Odds Ratio of 14 (confidence interval: 11-17), a risk/prevalence ratio of 8.5 and a risk/prevalence difference of 37.…”
Section: Sample Size Calculationmentioning
confidence: 99%